Beginning ASP.NET 4: in C# and VB - Spaanjaars, Imar (Wrox programmer to programmer, 2010)
This book is for anyone who wants to learn how to build rich and interactive web sites that run on the Microsoft platform. With the knowledge you gain from this book, you create a great foundation to build any type of web site, ranging from simple hobby-related web sites to sites you may be creating for commercial purposes.Anyone new to web programming should be able to follow along because no prior background in web development is assumed although it helps if you do have a basic understanding of HTML and the web in general. The book starts at the very beginning of web development by showing you how to obtain and install Visual Web Developer. The chapters that follow gradually introduce you to new technologies, building on top of the knowledge gained in the previous chapters.Do you have a strong preference for Visual Basic over C# or the other way around? Or do you think both languages are equally cool? Or maybe you haven't made up your mind yet and want to learn both languages? Either way, you'll like this book because all code examples are presented in both languages!Even if you have some experience with prior versions of ASP.NET, you may gain a lot from this book. Although many concepts from previous versions are brought forward into ASP.NET 4, you'll discover there's a lot of new stuff to be found in this book, including an introduction to the ADO.NET Entity Framework, the inclusion of jQuery, ASP.NET AJAX, the many changes to the ASP.NET 4 Framework, and much more.This book teaches you how to create a feature-rich, data-driven, and interactive web site called Planet Wrox. Although this is quite a mouthful, you'll find that with Visual Web Developer 2010, developing such a web site isn't as hard as it seems. You'll see the entire process of building a web site, from installing Visual Web Developer 2010 in Chapter 1 all the way up to putting your web application on a live server in Chapter 19. The book is divided into 19 chapters, each dealing with a specific subject.Chapter 1, "Getting Started with ASP.NET 4" shows you how to obtain and install Visual Web Developer 2010. You'll get instructions for downloading and installing the free edition of Visual Web Developer 2010, called the Express edition. You are also introduced to HTML, the language behind every web page. The chapter closes with an overview of the customization options that Visual Web Developer gives you.Chapter 2, "Building an ASP.NET Web Site" shows you how to create a new web site and how to add new elements like pages to it. Besides learning how to create a well-structured site, you also see how to use the numerous tools in Visual Web Developer to create HTML and ASP.NET pages.Chapter 3, "Designing Your Web Pages." Visual Web Developer comes with a host of tools that allow you to create well-designed and attractive web pages. In this chapter, you see how to make good use of these tools. Additionally, you learn about CSS, the language that is used to format web pages.Chapter 4, "Working with ASP.NET Server Controls." ASP.NET Server Controls are one of the most important concepts in ASP.NET. They allow you to create complex and feature-rich web sites with very little code. This chapter introduces you to the large number of server controls that are available, explains what they are used for, and shows you how to use them.Chapter 5, "Programming Your ASP.NET Web Pages." Although the built-in CSS tools and the ASP.NET Server Controls can get you a long way in creating web pages, you are likely to use a programming language to enhance your pages. This chapter serves as an introduction to programming with a strong focus on programming web pages. Best of all: all the examples you see in this chapter (and the rest of the book) are in both Visual Basic and C#, so you can choose the language you like best.Chapter 6, "Creating Consistent Looking Web